Activist Hedge Funds and Takeovers: Their Effects on Employment and Performance. (6th May 2021) - Kuvandikov, Azimjon; Pendleton, Andrew; Goergen, Marc
Abstract: This paper analyses the impact of activist hedge funds (AHFs) on post‐merger workforce downsizing and operating performance. AHFs have been widely criticized for achieving short‐term gains at the expense of other stakeholders, such as employees. The results show that AHF ownership and presence in acquiring firms is a significant determinant of post‐merger employment reductions. There is little evidence that these mergers and acquisitions have better operating performance relative to other takeovers. However, there is a negative effect of AHF ownership on labour productivity. Overall, the results are consistent with the view that AHF involvement in takeovers does not lead to sustained gains in performance.